2001
DOI: 10.1002/ana.1129
|View full text |Cite
|
Sign up to set email alerts
|

P0 protein is a target antigen in chronic inflammatory demyelinating polyradiculoneuropathy

Abstract: Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is widely regarded as an autoimmune disorder, although the autoantigen remains unknown. In this study, the sera of 21 CIDP patients were examined by immunofluorescence for antimyelin activity and by Western blotting for binding to myelin proteins. Six sera contained anti-P0 immunoglobulin G antibodies, and four of these caused conduction block and demyelination following intraneural injection in experimental animals. Absorption with P0 protein el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(95 citation statements)
references
References 32 publications
2
89
0
4
Order By: Relevance
“…In the study of Yan et al western immunoblot technique identified antibodies to P0 in six of 21 CIDP patients who were responsive to plasma exchange and only in one of 15 controls. 15 Allen and colleagues also found antibodies to P0-like bands by immunoblot in eight of 32 patients with CIDP and none in 30 normal controls. 16 However, Sanvito et al did not find a significant difference in the proportion of subjects with IgG anti-P0 peptides in patients with CIDP compared with controls, although individual subjects with CIDP had high titers.…”
Section: Dovepressmentioning
confidence: 98%
See 1 more Smart Citation
“…In the study of Yan et al western immunoblot technique identified antibodies to P0 in six of 21 CIDP patients who were responsive to plasma exchange and only in one of 15 controls. 15 Allen and colleagues also found antibodies to P0-like bands by immunoblot in eight of 32 patients with CIDP and none in 30 normal controls. 16 However, Sanvito et al did not find a significant difference in the proportion of subjects with IgG anti-P0 peptides in patients with CIDP compared with controls, although individual subjects with CIDP had high titers.…”
Section: Dovepressmentioning
confidence: 98%
“…22 Furthermore, the antibodies to P0 glycoprotein in Yan and colleagues' study were mainly IgG 1, a subclass that implies T-cell activation. 15 It is likely that both B and T-cell mechanisms are involved. More research is needed to establish the target of the T-cell response and whether other cell populations, like NK and T-cells are relevant to the pathogenesis of CIDP.…”
Section: Dovepressmentioning
confidence: 99%
“…No target has definitely been identified, although myelin protein P0 has been suggested. 1 Demyelination is multifocal and can involve the distal nerve terminals, intermediate nerve segments, and nerve roots. Cranial nerves are mildly affected in some patients.…”
Section: Case Historymentioning
confidence: 99%
“…One of the major causes is represented by mutations in the myelin protein zero (P0) 3 gene locus, which leads to Charcot-Marie-Tooth type 1B disorder or Dejerine-Sottas syndrome (1). Heterozygous and homozygous P0-deficient mice serve as animal models for these disorders.…”
mentioning
confidence: 99%